Magnitude and factors associated with low birth weight among newborns in public health facilities of Mekelle City, northern Ethiopia: a multi-center study - Teklehaimanot, Gebremichael Aregawi; Gebreslasie, Kahsay Zenebe; Werid, Woldu Mammo; Gebresilassie, Berhanu; Kidanemariam, Gebregziabher; Tsegay, Etsay Weldekidan; Gufue, Zenawi Hagos; Mengesha, Meresa Berwo (Frontiers in Pediatrics, 2024)
BackgroundLow birth weight is a key determinant of child survival, significantly influencing rates of infant and childhood mortality, morbidity, and disability. While some studies have been conducted in our region, there is still a gap in evidence regarding the maternal characteristics associated with low birth weight. Hence, this study aimed to determine the proportion of newborns with low birth weight and determinant factors, particularly focusing on maternal characteristics.MethodA facility-based cross-sectional study was conducted from 21 March to 20 April 2020 involving mothers and their newborns at selected public health facilities in Mekelle City. The sample included 447 participants, with two public hospitals and three health centers chosen by a lottery method. Systematic random sampling was applied to select mother–newborn pairs. Data were collected using a structured, interviewer-administered questionnaire and analyzed using the Statistical Package for Social Sciences version 21. Bivariate and multivariate logistic regression analyses, with a 95% confidence interval (CI), were used to identify factors associated with low birth weight.ResultsThe study included 447 mothers of newborns, achieving a 100% response rate. The proportion of low birth weight was 14.3%. Significant factors associated with low birth weight included attending the first antenatal care (ANC) visit in the third trimester [adjusted odds ratio (AOR) = 3.66, 95% CI: 1.28–10.44], not receiving additional nutrition during pregnancy (AOR = 4.16, 95% CI: 1.38–12.58), experiencing obstetric complications during the current pregnancy (AOR = 7.72, 95% CI: 2.76–21.59), and a gestational age at birth of less than 37 weeks (AOR = 5.36, 95% CI: 1.96–14.67).Conclusion and recommendationThis study revealed a substantial incidence of low birth weight. The initiation of the first antenatal care visit in the third trimester, failure to supplement nutrition during pregnancy, the occurrence of obstetric complications during pregnancy, and a gestational age at birth less than 37 weeks were all found to be significantly correlated with this condition. It is recommended that policymakers strengthen maternal and child health services, especially through the focused ANC program, to improve outcomes. Health facilities should promote awareness of the importance of initiating ANC visits early, with an emphasis on nutritional counseling throughout pregnancy.